2020
DOI: 10.1016/j.combustflame.2020.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of fuel chemistry effects on burning modes in turbulent premixed flames

Abstract: The present work quantifies the impact of fuel chemistry on burning modes using premixed dimethyl ether (DME), ethanol (EtOH) and methane flames in a backto-burnt opposed jet configuration. The study considers equivalence ratios 0 ≤ Φ ≤ 1, resulting in a Damköhler (Da) number range 0.06 ≤ Da ≤ 5.1. Multi-scale turbulence (Re 19,550 and Re t 360) is generated by means of a cross fractal grid and kept constant along with the enthalpy of the hot combustion products (T HCP = 1700 K) of the counterflow stream. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…The soot layer thickness increases significantly with a decreasing rate of strain and increasing equivalence ratio with the flames becoming bright yellow/orange at ϕ U N = 2.2 and a T = 255 s −1 . Hampp and Lindstedt [52] have shown that the impact of the HCP temperature is comparatively modest for fuel-lean self-sustained flames that detach from the stagnation plane. The influence on soot formation is investigated below.…”
Section: Variationmentioning
confidence: 99%
“…The soot layer thickness increases significantly with a decreasing rate of strain and increasing equivalence ratio with the flames becoming bright yellow/orange at ϕ U N = 2.2 and a T = 255 s −1 . Hampp and Lindstedt [52] have shown that the impact of the HCP temperature is comparatively modest for fuel-lean self-sustained flames that detach from the stagnation plane. The influence on soot formation is investigated below.…”
Section: Variationmentioning
confidence: 99%
“…1, has advantages for the study of soot formation including the control of chemical and flow timescales [31]. The back-to-burnt (or fresh-to-burnt) configuration offers aerodynamic flame stabilisation [32], accurate boundary conditions [33] and a turbulent flowfield that is free of bulk instabilities [34,35]. The nozzle separation is set to the burner diameter for (close to) optimal flow stability [36].…”
Section: Burner Configuration and Experimental Conditionsmentioning
confidence: 99%